REDUCING ELECTRICITY CONSUMPTION FOR IRON AND STEEL SMELTING - L. E. Rovin; S. L. Rovin (Литьë и металлургия, 2013)
It is shown that the introduction of high-temperature heating installation charge fusion provides increased security, stability of operation arc, reduced noise to 75–85 dB, the elimination of fugitive emissions in the work zone